Pemberdayaan homestay warga dalam mendukung keberlanjutan ekowisata Keranggan - Rudy Pramono; Ira B Hubner; Juliana Juliana; Wulan Meiaya Wowor; Samuel Musa Liha (IKIP SILIWANGI, 2023)
Community service is an activity of practicing knowledge for the community in order to add insight and skills. The development of Kampung Keranggan ecotourism activities is showing encouraging results with the increasing number of visitors and activities being held at that location. However, there are still inadequate accommodation facilities for guests staying at these locations. Therefore this community service activity is carried out with the aim of: (1) Helping the community improve the quality of homestays (tourist lodges) as a means of educating tourists about the environment (2) Providing knowledge and skills for homestay owners / managers to be able to provide the best service and comfort for guests , in order to support the management of tourist villages and the welfare of the surrounding community. The results of community service activities can be concluded that the community's understanding of how to manage a homestay has increased, especially in maintaining the cleanliness and comfort of the home and how to manage food for homestay guests.